Pallet Use and Transport in Italy: Comparing the Carbon Footprints of Standard Exchange and Nolpal’s Alternative Strategy - Giovanni Dotelli; Paola Gallo Stampino; Edoardo Simonetti (Applied Sciences)
As global trade continues to intensify, the role of pallets becomes increasingly crucial, as they are essential for the movement of goods worldwide. Wooden pallets are the most common packaging type in Italy and Europe, and their widespread use in distribution and freight transportation means that the relatively minor environmental impact of an individual pallet is greatly magnified by the overall scale of operations. The management of pallets can significantly influence both the emissions and the costs associated with pallet operations. This work presents a case study representative of the emerging trends in sustainable transportation and logistics in Italy, aiming to compare the carbon footprint of the standard pallet exchange system with the system employed by the company Nolpal. Unlike the conventional exchange model, which requires companies to purchase and own EPAL pallets, Nolpal provides leased pallets to the market across Italy, supported by a nationwide network of collection hubs. A comparative life cycle assessment (LCA) between the Nolpal system and the conventional pallet exchange system showed that Nolpal’s approach achieves a 35% reduction in CO2-eq emissions. These findings highlight how the company’s model could serve as a blueprint for future advancements in more sustainable pallet management strategies.